Variability of behaviour in electricity load profile clustering: who does things at the same time each day? - Dent, Ian; Craig, Tony; Aickelin, Uwe; Rodden, Tom (Springer International Publishing, 2014)
UK electricity market changes provide opportunities to alter households' electricity usage patterns for the benet of the overall electricity network. Work on clustering similar households has concentrated on daily load proles and the variability in regular household behaviours has not been considered. Those households with most variability in reg- ular activities may be the most receptive to incentives to change timing. Whether using the variability of regular behaviour allows the creation of more consistent groupings of households is investigated and compared with daily load prole clustering. 204 UK households are analysed to nd repeating patterns (motifs). Variability in the time of the motif is used as the basis for clustering households. Dierent clustering algorithms are assessed by the consistency of the results.